Recombinant expression and functional characterization of influenza A virus neuraminidase in a mammalian cell system - Huang, Ailing; Liu, Yulong; Li, Yanbai; Yin, Zhe; Huo, Shanshan; Wang, Juan; Yang, Zhenlin; Ying, Tianlei; Yu, Fei (Frontiers in Microbiology, 2025)
The soluble and functional expression of influenza A virus neuraminidase (NA) remains a major challenge due to its membrane-associated nature and structural complexity. In this study, we established a mammalian expression strategy that enables the production of correctly folded, enzymatically active NA proteins across multiple influenza A subtypes. Through systematic N-terminal deletion mapping, we identified a conserved structural boundary within the transmembrane-stalk region that critically determines NA solubility. Truncation of approximately 65–80 amino acids, combined with enforced tetramerization via a human VASP domain, allowed efficient secretion of stable tetrameric NAs in Expi293 cells. The resulting proteins displayed native-like mushroom-shaped symmetry under electron microscopy, exhibited robust enzymatic activity, and retained high binding affinity to the broadly protective antibody 1G01. Immunization with tetrameric NAs elicited strong humoral responses targeting conserved epitopes in the enzymatic active center in mice, indicating that tetrameric NA vaccines efficiently induce protective antibodies. These findings define the structural determinants required for soluble and immunogenic NA expression, and provide a versatile platform for the development of broad-spectrum influenza vaccines and antiviral agents.